2012
DOI: 10.1016/j.ijosm.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic lymphatic pump techniques to enhance immunity and treat pneumonia

Abstract: Pneumonia is a common cause of morbidity and mortality worldwide. While antibiotics are generally effective for the treatment of infection, the emergence of resistant strains of bacteria threatens their success. The osteopathic medical profession has designed a set of manipulative techniques called lymphatic pump techniques (LPT), to enhance the flow of lymph through the lymphatic system. Clinically, LPT is used to treat infection and oedemaand might be an effective adjuvant therapy in patients with pneumonia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Although the lymphatic intrinsic pumping function is considered important for maintaining the homeostasis of interstitial fluid and molecule balances in local tissue and may be critical for total body health, 3,4 the effect of reduced lymphatic pumping pressure (P lp ) in the legs on general health has not been studied. Many people complain of leg edema in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Although the lymphatic intrinsic pumping function is considered important for maintaining the homeostasis of interstitial fluid and molecule balances in local tissue and may be critical for total body health, 3,4 the effect of reduced lymphatic pumping pressure (P lp ) in the legs on general health has not been studied. Many people complain of leg edema in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Both mechanisms could potentially enhance immunity to infectious disease. It is important to mention that while we have shown Ab-LPT enhances the concentration of lymphatic leukocytes and inflammatory mediators, [15][16][17][18][19] the effect of Th-LPT on lymphatic immune cells has not been measured. However, Th-LPT has been shown to increase the lymphatic uptake of antigen in rats 13 and thoracic duct lymph flow in dogs.…”
Section: Discussionmentioning
confidence: 79%
“…10,19 Twentyfour hours after infection, rats were divided into control, sham, and abdominal LPT (Ab-LPT) or thoracic LPT (Th-LPT) groups. For 3 consecutive days, the control group received no treatment or anesthesia, the sham group received 4 min of light touch (under anesthesia), and the Ab-LPT and Th-LPT groups received 4 min of LPT (under anesthesia).…”
Section: Ab-lpt and Th-lpt Reduce S Pneumoniae Cfu In The Lungsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in support, recent animal studies demonstrated LPT has a positive effect on infection 40 and edema. 19 Some limitations of the current study must be recognized.…”
Section: -36mentioning
confidence: 88%